Analisis Model E-Bisnis B2C ada Perusahaan Teknologi di Indonesia - Sikki, Nurhaeni; Gerhana, Hana; Herlaman, Jendry; Ratih, N.; Liana, Lia; Permana, Iskandar; Tija, Irmansyah; mirzaq, mirzaq (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
This study aims to analyze the B2C e-business model implemented by technology companies in Indonesia and identify the factors influencing its success and the challenges faced during its implementation. The B2C (Business-to-Consumer) e-business model has grown rapidly with internet penetration and smartphone usage in Indonesia. Additionally, government policies and the digitalization of SMEs have been key factors in the country's growth of the e-commerce industry. This research uses a literature review and descriptive analysis method, gathering secondary data from industry reports, journals, and data from leading e-commerce companies in Indonesia. The results show that the success of the B2C model in Indonesia is significantly influenced by consumer trust, intense competition between companies, and the logistical infrastructure that remains a challenge. Furthermore, technologies such as AI and blockchain can enhance the customer experience and improve data management systems. Large companies like Tokopedia and Bukalapak have demonstrated that the development of the right strategy can help them maintain their market share. Still, they also face challenges related to declining profit margins due to aggressive customer acquisition strategies. Looking ahead, global market expansion and the empowerment of SMEs will be crucial to ensuring sustainable growth for the B2C e-business model in Indonesia. This study is expected to provide insights for policymakers and industry players in formulating more effective strategies to optimize the potential of e-commerce in Indonesia.